40 Changes in prescription routines for treating hypothyroidism between 2001 and 2015 – a population-based study of 929, 684 primary care patients in copenhagen. (20th August 2018) - Medici, Bjarke; Nygaard, Birte; Cour, Jeppe la; Grand, Mia; Siersma, Volkert; Nicolaisdottir, Dagny; Lind, Bent; Olivarius, Niels; Andersen, Christen
Abstract : Objectives: Primary objective: To investigate changes in s-TSH threshold used by the general practitioners to initiate L-T4 therapy over the period 2001–2015 in Copenhagen. Method: Primary objective Retrospective analysis of all s-TSH measurements between 2001 and 2015 performed at the general practitioners' joint laboratory merged with The Danish Register of Medicinal Products Statistics and The Danish National Patient Registry. For each year in the period the estimated treatment threshold was calculated from the s-TSH measurements performed in that year as the level of s-TSH where the estimated probability of starting L-T4 therapy is 50%. Also the median level s-TSH at therapy initiation was recorded for each year. Results: 929 684 individuals with 2 975 277 s-TSH measurements were included for the calculations. While the size and composition of the population serviced by the general practitioners remained virtually unchanged throughout the 15 year period, the number of performed s-TSH measurements increased from 110 886 in 2001 to 292 911 in 2015 and the number of patients initiating L-T4 therapy increased from 786 in 2001 to 1825 in 2015. The median s-TSH at L-T4 therapy initiation decreased from 10 mU/l (IQR 5.2–29.7) in 2001 to 6.8 mU/l (IQR 5.1–11) in 2015, while the estimated treatment threshold decreased considerably from 28.3 (95% CI 21.0 to 40.2) mU/l in 2001 to 14.2 (95% CI 12.0 to 18.0) in 2007 where it remained relatively unchanged for the rest of the study period. Conclusions: This study performed on a sizeable primary care population demonstrates a considerable fall in the s-TSH threshold when initiating L-T4 therapy in hypothyroid patients, while the number of patients with s-TSH of 5–10 mU/l starting therapy increased considerably. Measuring TPO-antibodies appears to have influenced the s-TSH threshold considerably. The study also reveals that intensified TSH measuring from the 2010 level to the 2015 level did not lead to any further discoveries of hypothyroidism cases suggesting that very few hypothyroid persons remain undiagnosed.